Design features of modern furniture-transformer - Kuznetsova, I.; Us, V.; Zalizko, Y. (Theory and practice of design, 2016)
Features furniture-transformer structures depend on the product and the idea of functionality. Development furnituretransformers with multiple functions and transformations appearance was due to a limited area of housing. It was found the main types of modern furniture design solutions transformers, frame, safety frame, mounted skeleton.